Manganese-catalyzed Sonogashira coupling of aryl iodides. Issue 15 (13th April 2016) - Qi, Xinxin; Jiang, Li-Bing; Wu, Xiao-Feng
Graphical abstract: Highlights: Manganese-catalyzed Sonogashira coupling. With PEG-400 as the green solvent. Good functional group tolerance and good yields. Abstract: An interesting manganese-catalyzed Sonogashira coupling reaction of aryl iodides has been developed. With PEG-400 as the green solvent and under mild reaction conditions, a variety of diarylacetylenes were obtained in moderate to good yields.